Cardiac protection induced by urocortin-2 enables the regulation of apoptosis and fibrosis after ischemia and reperfusion involving miR-29a modulation - Isabel Mayoral-González; Eva M. Calderón-Sánchez; Isabel Galeano-Otero; Marta Martín-Bórnez; Encarnación Gutiérrez-Carretero; María Fernández-Velasco; Nieves Domenech; María Generosa Crespo-Leiro; Ana María Gómez; Antonio Ordóñez-Fernández; Abdelkrim Hmadcha; Tarik Smani (Elsevier, 2022)
Urocortin-2 (Ucn-2) has demonstrated cardioprotective actions against myocardial ischemia-reperfusion (I/R) injuries. Herein, we explored the protective role of Ucn-2 through microRNAs (miRNAs) post-transcriptional regulation of apoptotic and pro-fibrotic genes. We determined that the intravenous administration of Ucn-2 before heart reperfusion in a Wistar rat model of I/R recovered cardiac contractility and decreased fibrosis, lactate dehydrogenase release, and apoptosis. The infusion of Ucn-2 also inhibited the upregulation of 6 miRNAs in revascularized heart. The in silico analysis indicated that miR-29a and miR-451_1∗ are predicted to target many apoptotic and fibrotic genes. Accordingly, the transfection of neonatal rat ventricular myocytes with mimics overexpressing miR-29a, but not miR-451_1∗, prevented I/R-induced expression of pro- and anti-apoptotic genes such as Apaf-1, Hmox-1, and Cycs, as well as pro-fibrotic genes Col-I and Col-III. We also confirmed that Hmox-1, target of miR-29a, is highly expressed at the mRNA and protein levels in adult rat heart under I/R, whereas, Ucn-2 abolished I/R-induced mRNA and protein upregulation of HMOX-1. Interestingly, a significant upregulation of Hmox-1 was observed in the ventricle of ischemic patients with heart failure, correlating negatively with the left ventricle ejection fraction. Altogether, these data indicate that Ucn-2, through miR-29a regulation, provides long-lasting cardioprotection, involving the post-transcriptional regulation of apoptotic and fibrotic genes.